The analysis of the residual amount of pesticides in grapes and their biochemical indicators. - Yolchueva Emina Agil, Huseynova Sevinj Hidayat, Mammadova Aytan Azar, Osmanova Sevda Yashar (South Eastern European Journal of Public Health, 2025)
The article examines the three grape varieties –Tabrizi, Cardinal and Italian Muscat from the grape sites of the Ganja-Gazakh region of Azerbaijan. The analyses of pesticides in these varieties carried out in the laboratory of the Chemistry department, of Azerbaijan State Agricultural University and Azerbaijan Institute of Food Safety. The qualitative determination of organic pesticides containing a phenyl and pyrimidine ring was performed on the GC-MS QP 2020 analyzer.